Construcción del concepto de pareja en hijas de madres solteras sin un referente paterno (2019)
The present research work tries to determine the effects that the absence of the father can have in the election of a couple in daughters of single mothers, which have been abandoned by their spouse. A descriptive study of women is carried out since it is sought to analyze the construction of the concept of a couple taking into account the characteristics of the participants who reside in the cities of Bogotá and Medellín. Semi-structured open interviews were conducted individually and the information was analyzed through three descriptive categories: their own relationship with their father, emotional relationships and parenting and family.